Trees First Inhibit Then Promote Litter Decomposition in the Subarctic - Jonsson, Micael; Clemmensen, Karina E.; Castaño, Carles; Parker, Thomas C. (Wiley-Blackwell, 2025)
Trees affect organic matter decomposition through allocation of recently fixed carbon belowground, but the magnitude and di-rection of this effect may depend on substrate type and decomposition stage. Here, we followed mass loss, chemical compositionand fungal colonisation of leaf and root litters incubated in mountain birch forests over 4 years, in plots where belowground car-bon allocation was severed by tree girdling or in control plots. Initially, girdling stimulated leaf and root litter mass loss by 12%and 22%, respectively, suggesting competitive release of saprotrophic decomposition when tree-mediated competition by ectomy-corrhizal fungi was eliminated (Gadgil effect). After 4 years, girdling instead hampered mass loss of root litter by 30%, suggestinglate-stage priming of decomposition in the presence of trees, in parallel with increased growth of shrubs and associated fungifollowing tree elimination. Hence, different mechanisms driving early- and late-stage litter decomposition should be consideredin climate-feedback evaluations of plant–soil interactions.
Keywords: ectomycorrhizal fungi; ericaceous shrubs; Gadgil effect; leaf litter; mountain birch; priming; root litter; saprophytic fungi; treeline; tundra